Empowering Communities in Cengkareng through Online Learning: Unveiling the Potential of News Portal Nachannel.my.id - Mohamad Firdaus; Aditya Herliawan; Fatoni Fatoni; Aldiansyah Aldiansyah (Lembaga Riset dan Inovasi Masyarakat Madani, 2023)
In the contemporary era, news portals have become integral mediums for global information access and dissemination. However, the swift evolution of technology demands a nuanced understanding to effectively harness these platforms. This study employs an online learning approach as part of a community service initiative, targeting the residents of Komplek Kebersihan Street 13th Neighbourhood 10th Hamlet in Cengkareng, West Jakarta. Focused on the news portal Nachannel.my.id, this endeavor not only familiarizes participants with its features but also addresses the imperative of technological literacy in engineering education. By providing insights into news portal functionality and usage, the initiative empowers participants to navigate the digital information landscape proficiently. The study's outcomes underscore the significance of bridging the knowledge gap, as post-service feedback reflects enhanced awareness and appreciation for the advantages conferred by news portals. This research contributes to the field of engineering by emphasizing the pivotal role of technological literacy in engaging with contemporary information platforms.